Ecobrick meja : solusi inovatif mengatasi masalah sampah plastik - Rohmah, Ayyu Nur; Ita'ufaidilah, Salvi (Maliki Interdisciplinary Journal, 2025)
The problem of waste has become a classic problem that continues from time to time, both in Indonesia and in various pasrts of the world. As a developing country, Indonesia should pay special attention to this issue, especially plastic waste which is one of the most concering waste. Plastic is widely used in various aspects of human life, from food packaging to automotive industry materials. As a material, plastic is one of the most popular and most seriously used ins the manufacture of automotive components, besides metals such as iron. However, the main problem caused by plasticis its waste which is very difficult to decompose naturally. In addition, the increasingly uncontrolled use of plastic worsens the situation. In addition, the nature of plastic which is made of polymer and is not porous causes an increase in air temperature over time. Currently, most products are still produced without considering without considering their impact after use. One environmentally friendly solution to evercome plastic waste is with ecobricks, which is managing plastic waste into useful objects such as chairs, tables, and so on. The making of ecobricks is not yet widely known or applied by the community. The majority of people still consider used plastic as ordinary household waste, which is then disposed of carelessly, polluting the environment and disrupting daily life without any awareness of its impact.